Health Education and Uric Acid Examination for the Elderly in Region IV Pasar 0, Working Area of Lubuk Pakam Health - Saragih, Astri Ulina; Ginting, Desideria Yosepha; Turnip, Meria; Yulanda, Risky; Natalia, Santa (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2025)
Hyperuricemia, or elevated uric acid levels in the blood, is a common condition among the elderly and may lead to gout arthritis, a painful inflammatory joint disease. This condition is closely related to other degenerative diseases such as hypertension, diabetes mellitus, metabolic syndrome, and cardiovascular disorders. Global data indicate that the prevalence of gout in the elderly reaches 2,505.4 per 100,000 people, making it a significant public health concern. In Indonesia, the prevalence of hyperuricemia in the elderly varies by region, with some reporting up to 18.6%. In Deli Serdang Regency, specifically in Namorih Village, Pancur Batu Subdistrict, a study found that 42.5% of elderly individuals had elevated uric acid levels .This community service aimed to increase awareness and knowledge among the elderly about the prevention and management of hyperuricemia through health education. The method used was an interactive educational session that included lectures and discussions. The activity took place on Apr22, 2025, in Region IV under the working area of Lubuk Pakam Health Center, involving 20 elderly participants.The results showed a significant increase in participants' understanding regarding healthy lifestyle choices, including low-purine diets, regular physical activity, and the importance of regular uric acid screening. Active engagement during discussions demonstrated the participants' enthusiasm to apply the knowledge in their daily routines. .In conclusion, health education using lecture and discussion methods proved effective in enhancing elderly awareness regarding hyperuricemia prevention and control. Similar activities are recommended to be conducted regularly in other regions to improve elderly quality of life .